Effectiveness of Lactic Acid Bacteria to Improve Cyprinus carpio Fingerlings Resistance Against - Rosidah Rosidah; Yuniar Mulyani; Walim Lili; Khasanatur Rosyidah (UIN Sunan Gunung Djati Bandung, 2020)
Common carp (Cyprinus carpio) cultivation is often hampered by a disease attack, one of them is the attack of Edwarsiella tarda. Lactic acid bacteria (LAB) can be used as an alternative to prevent diseases in fish by increasing the body's resistance. This research aimed to determine the most effective isolates of LAB that increase of the resistance of carp fingerlings to the attack of E. tarda bacteria and see which isolates can produce the highest survival. The LAB isolates used were the result of isolation from the gut of carp. This study used a Completely Randomized Design (CRD) consisting of four treatments with three replications. The fish were immersed with different LAB isolates, CcB7, CcB8, and CcB15 in the same density of 108 cells / mm3. Immersion was carried out for 30 minutes with a frequency of seven days. While during the research, two immersions were carried out before the challenge test against E. tarda bacteria. The parameters observed were the number of leukocytes, hematocrit, erythrocyte, differential leukocytes, survival rate, and clinical symptoms that appeared. The results showed that all LAB isolates used in this study could increase the body resistance of carp against the attacks of E. tarda bacteria. The LAB CcB7 isolate was the most effective for enhancing the body resistance of carp fish withthe highest increase level of leukocyte, erythrocyte, and hematocrit were 18 ± 0.057,7 ± 0,077, and 0.26± 7.31% respectively. After being challenged with E. tarda bacteria producing mild clinical symptoms, the highest increase is in monocyte and neutrophil cells was 20 and 62% respectively, the highest reduction in lymphocytes was – 9% and the highest survival rate was 80%.